Green manufacturing of nanostructured Al-Based sustainable self-cleaning metallic surfaces. (1st January 2021) - Mandal, Priya; Perumal, Gopinath; Arora, Harpreet S.; Ghosh, Sajal K.; Grewal, Harpreet S.
Abstract: Atmospheric degradation of the metallic components initiated by the accumulation of contaminants and humidity significantly limits the performance and sustainability of many engineering systems. Aluminium and its alloys are widely used in different industries such as food processing, marine, aerospace, automobiles and household appliances. The leaching of aluminium can cause significant environmental and health-related issues. In the present study, a facile and environment-friendly (hot water treatment) processing route was utilized to fabricate sustainable Al surfaces without the use of any chemical reagents and toxic solvents. The developed nanostructured Al surface showed immense mechanical, chemical and thermal durability restricting corrosion and leaching of aluminium. The processed Al composed of self-assembled 2D nanostructures showed extreme wettability ranging from superhydrophilic (θ < 5°) to superhydrophobicity (SHS) (θ > 160°), depending upon post-processing conditions. The developed SHS has showed high water (droplet impacts) and dust repellence under static and dynamic conditions. This is related with effective entrapment of air, prompted by the presence of nanostructured morphology, leading to stable Cassie state. Results showed that SHS possess better self-cleaning ability compared to the superhydrophilic counterpart. The SHS showed better sustainability in terms of high thermal stability in a temperature range of −80 °C to 350 °C and corrosion resistance under prolonged immersion for 48 h in salt media. Compared to unprocessed counterpart, SHS showed 40 times reduction in the corrosion rate, which is significantly high when compared with several other processing routes. The present study showed an eco-friendly and straightforward approach which can be effectively used for fabricating multifunctional metallic surfaces with widespread applications. Graphical abstract: Image 1 Highlights: Simple and eco-friendly method used to develop sustainable self-cleaning surface. Superhydrophobic aluminium surface was fabricated using simple hot water treatment. Self-assembled nanostructures showed extreme wetting states based on post treatment. Fabricated surface showed excellent corrosion resistance and thermal stability.